Interoception abnormalities in schizophrenia: A review of preliminary evidence and an integration with Bayesian accounts of psychosis. (January 2022) - Yao, Beier; Thakkar, Katharine
Highlights: Alterations may exist across various interoceptive systems in schizophrenia. Interaction between interoception and exteroception may be altered in schizophrenia. Interoceptive inference theory is a new framework to interpret existing literature. Altered interoceptive inference may contribute to negative and positive symptoms. Research on interoceptive inference in schizophrenia may lead to new treatment. Abstract: Schizophrenia research has traditionally focused almost exclusively on how the brain interprets the outside world. However, our internal bodily milieu is also central to how we interpret the world and construct our reality: signals from within the body are critical for not only basic survival, but also a wide range of brain functions from basic perception, emotion, and motivation, to sense of self. In this article, we propose that interoception—the processing of bodily signals—may have implications for a wide range of clinical symptoms in schizophrenia and may thus provide key insights into illness mechanisms. We start with an overview of interoception pathways. Then we provide a review of direct and indirect findings in various interoceptive systems in schizophrenia and interpret these findings in the context of computational frameworks that model interoception as hierarchical Bayesian inference. Finally, we propose a conceptual model of how altered interoceptive inference may contribute to specific schizophrenia symptoms—negative symptoms in particular—and suggest directions for future research, including potential new avenues of treatment.